A perspective research on professional abilities of mentor principals - Shen, Chien-Huei; Cheng, Hsin-Hui; Chen, Pi-Ching (Technium Social Sciences Journal, 2022)
The purpose of this study is to explore the professional abilities of mentor principals for filling the gaps in educational management and management discipline knowledge. The research results show that the professional abilities of mentor principals include five aspects: building trust, guiding practice, paying attention to learners, integrating resources, and professional growth. Building trust includes two dimensions: the characteristics of mentor and coaching ability; guiding practice includes administrative leadership and cultural shaping; focusing on learners includes teaching leadership and learning leadership; integrating resources includes resource application and school marketing; professional development includes development orientation and development approaches. The findings of this study would be applied to educational administration and leadership.